Quantum confinement chemistry of CdS QDs plus hot electron of Au over TiO2 nanowire protruding to be encouraging photocatalyst towards nitrophenol conversion and ciprofloxacin degradation. Issue 1 (February 2019) - Kandi, Debasmita; Behera, Arjun; Martha, Satyabadi; Naik, Brundabana; Parida, K.M.
Graphical abstract: The quantum size effect of CdS QD, hot electron transfer of Au and suitable band alignment are mainly responsible for enhanced photocatalytic activity of TiO2 /Au/CdS QDs nanocomposite Highlights: TiO2 nanowire is synthesized and modified with Au nanoparticles and CdS QDs. UV-Vis DRS confirms the plasmonic direct hot electron transfer (DET) mechanism. Longer life time of electrons is found 97.4 μs from Bode phase plot for TiO2 /1%Au/3%CdS QDs nanocomposite. Photocatalytic conversion of 2-NP and 4-NP to respective amino phenols shows a conversion rate of 99% and 67.68% respectively. Degradation rate of 99.4% is observed for ciprofloxacin. Abstract: Solar light harvesting science is ascertained to be the topmost effective green technique in alleviating environmental pollutants. In this respect, we report a visible light active TiO2 /Au/CdS QDs nanocomposite which manifested upgraded photocatalytic activity towards the transformation of 2-nitrophenol, 4-nitrophenol, and degradation of ciprofloxacin. Here, TiO2 nanowire is synthesized by a molten flux method with high product yield and crystallinity with organized dimensions. Au nanoparticles are successfully integrated in between TiO2 -CdS composite by Reverse Turkevich method. The prepared composites are meticulously characterized by different physical and optoelectronic techniques to inspect the crystal structure, phase purity, optical properties, nanostructured morphology and electrochemical properties. The plasmonic direct hot electron transfer (DET) mechanism is confirmed from UV-Vis DRS spectra. The prepared composite produces 2.98 mA/cm 2 of current density under light irradiation. A Longer lifetime of electrons is found from Bode phase plot i.e. 97.4 μs for TiO2 /1%Au/3%CdS QDs owing to the integrative cooperation effect of high aspect ratio of TiO2 nanowire, quantum size effect of CdS and the direct hot electron transfer by Au nanoparticle.